LOW-CYCLE FATIGUE OF COLD-DRAWN TYPE 304 AUSTENITIC STAINLESS STEEL IN ANNEALING CONDITIONS - Ambar Pambudi; Mohammad Badaruddin; Sugiyanto Sugiyanto (Asosiasi Peneliti Sriwijaya, 2022)
Type 304 austenitic stainless steel, or better known as SS304, generally has alloying elements: C < 0.1%, Cr 18 – 20%, Fe 66 – 74%, Mn <2%, Ni 8 – 10.5%, P <0.045%, Si <1%, and S <0.030%. In general, this material has good ductility, high tensile strength, and excellent corrosion resistance. In application, type SS304 will be subjected to repeated loading, and eventually, the material will undergo plastic deformation, which leads to structural failure in a short life. The failure of SS304 is generally due to the inability of the material to repeat loading, which results in large amounts of plastic deformation so that the SS304 will experience fatigue and then fracture. Based on the description above, this study aims to evaluate the LCF properties of 304 CDS stainless steel with annealing heat treatment. The parameter used was the strain amplitude 0.003 – 0.013 mm/mm. The results of this study revealed that the highest fatigue life in the LCF test was experienced by steel with heat treatment at an amplitude of 0.003 mm/mm with 48367 cycles. In contrast, at the amplitude condition of 0.013 mm/mm, the fatigue life of the steel decreased drastically with the resulting plastic strain being larger, namely 0.0094 mm/mm and elastic strain of 0.0035 mm/mm, with an average modulus of elasticity of 194 GPa. Annealing treatment conditions experienced decreased mechanical strength but tended to be ductile. Using Basquin-Coffin-Manson Equation, empirical equations to predict LCF of 304 stainless steels can be determined.